Uji Aktivitas Antioksidan Green dan Roasted Biji Kopi Robusta Temanggung Menggunakan Metode DPPH - Mega Putri (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2023)
Oxidative stress can cause cell damage if endogenous antioxidants cannot fight free radicals.If the cell damage lasts a long time, it can cause premature aging and disease disordesa such ascancer, cardiovascular disease, and diabetes.To assists endogenous antioxidants in fighting free radicals, exogenous antioxidants can help. One of them is coffee. However, the content of compoundscontained in coffee can be affected by the roasting process. The degree of the roasting process can affect the physical properties, taste, aroma, and chemical content of coffee beans. Changes in the chemical content of coffee beans can affect antioxidant avtivity, This study aims to determine the effect of roasting degree on antioxidant activity of Temanggung Robusta coffee beans. Robusta coffee bean samples were identified to ensure the correctness of the sample, than macerated with 1:10 aquadest. The filtrate was tested for antioxidants using the DPPH method, which later obtained the LC50 value. Identification results obtained that the correct sample is robusta coffee beans. The antioxidant test results showed that LC50 og green, light, medium, and dark beans were 82,27, 362,91, 61,46, and 617,04. Based on these results, it is known that the best antioxidant activity is medium bean. Changes in the antioxidant capacity of roasted coffee beans are related to the degradation of chlorogenic acid, melanoidin, and Maillard’s reaction products.